Larvae-Free Rate Aedes sp: The Effect of Temperature, Humidity and Rainfall in Bengkulu City, Indonesia - Gunasari, Lala Foresta Valentine; Aladdawiyah, Zahara Septika; Suwarsono, Suwarsono; Triana, Dessy (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2024)
Abstract Background: Bengkulu's tropical climate is very suitable for Ae. aegypti and Ae. albopictus mosquito breeding. Temperature, humidity and rainfall affect mosquito breeding and dengue virus proliferation in mosquitoes, which in turn had an effect on the dengue infections. Dengue prevention strategy currently focuses on vector control with the Larvae Free Rate (LFR) parameter. This study aimed to determine environmental factors affecting the LFR in 2022 in Bengkulu City, Indonesia.Methods: This research used a cross-sectional study design with time series analysis. Time series was used to analyze and interpret sequential data points collected over the interval of time. Secondary data about LFR was obtained from the Bengkulu City Health Service, and climate variables from the Climatology Station of the Bengkulu Meteorology, Climatology, and Geophysics Agency. Data analysis was conducted through simple linear regressions.Results: The average of LFR in Bengkulu City in 2022 was 78.13% (below the national target), with the highest in December (87.85%) and the lowest in May (68.53%). The average temperature, humidity, and rainfall were 26.88°C (moderate), 83.5% (moderate), and 328.96% (high), respectively. The simple linear regression analysis showed that the effect of temperature, humidity, and rainfall was significant to LFR with the respective p-values of 0.010; 0.612, and 0.173).Conclusion: Temperature influenced the LFR by 58,5% but humidity and rainfall have no effect on LFR of Aedes spp. in Bengkulu City in 2022. High temperatures will increase the risk of transmission of dengue virus infection by 3-5%.